Confusion of Insulinoma’s Neuroglycopenic Symptoms with Epilepsy, Two Case Presentation and a Review of Literature - Gokosmanoglu, Feyzı; Colak, Ramis (My University, 2018)
Insulinoma is a pancreatic endocrine tumour which origins from beta cells and characterized by excessive insulin secretion and hypoglycemia due to this. Symptoms seen in hypoglycemia are due to brain’s lack of glucose (neuroglycopenia) such as somnolence, irritability, confusion, abnormal behaviour, epileptic seizure and even coma. In this study, we presented two insulinoma cases who applied to our clinic with neuroglycopenic symptoms. Patients followed up with epilepsy diagnosis were referred to us because of low blood glucose rates. Hyperinsulinemic hypoglycemia in the prolonged fasting test and a mass in pancreas were detected in both patients and so they were diagnosed as insulinoma. The mass was excised by laparoscopic ways in surgical clinic and patients clinic were completely recovered postoperative. In conclusion, it is necessary to determine whether there is an underlying organic brain lesion or a metabolic condition in order to prevent long-term use of unnecessary antiepileptic in patients presenting with seizures.
Keywords: Genel ve Dahili Tıp; Patoloji; Gastroenteroloji ve Hepatoloji